STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN AKHLAK SISWA MELALUI PENDEKATAN KETELADANAN - Harmita, Yulia; Yumna; Zulmasri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on the preliminary observation conducted at SD Negeri 27 Sungai Nanam on September 1, 2025, it was found that there were obstacles in the formation of students’ morals and character. This study aims to determine the results of implementing the exemplary strategy used by Islamic Religious Education teachers in shaping students’ morals at SD Negeri 27 Sungai Nanam. The type of research used is qualitative research with a case study method. The main informants consisted of Islamic Religious Education teachers, the principal, and students. Data were collected through interviews, observations, and documentation, then analyzed through the stages of data reduction and data presentation. The findings of the study indicate that the strategies implemented by the Islamic Religious Education teachers at SD Negeri 27 Sungai Nanam faced several obstacles in the application of the exemplary approach. In addition, parental factors also influenced the implementation process, so that the execution of the strategy had not been fully in accordance with the objectives of moral and character formation.